Effet Des Rejets De La Station De Dessalement Sur La Modification Des Paramètres Physico Chimique D’oued El Mactaa. - ABDELI, ZIAD; BOUCHELIL, FOUAD (My University, 2022)
The main objective of our work is to include the assessment of the level of pollution of desalination stations at the level of wastewater and Oued el Mactaa. This study is based on the analysis of physico-chemical parameters. The most commonly used method is desalination and we describe the reverse osmosis desalination plant of El-Mactaâ (Willaya in Mostaganem) and its impact on the environment. The results obtained show significant variations in the physico-chemical parameters. The monitoring of variations in physico-chemical parameters has yielded varied results. The ph and the conductivity studied with high levels reveal a permanent population
Keywords: pollution; sea water; physicochemical parameters; reverses osmosis; desalination